An Extracellular Tetrathionate Hydrolase from the Thermoacidophilic Archaeon Acidianus Ambivalens with an Activity Optimum at pH 1 - Protze, Jonas; Müller, Fabian; Lauber, Karin; Naß, Bastian; Mentele, Reinhard; Lottspeich, Friedrich; Kletzin, Arnulf (Frontiers in Microbiology, 2011)
Background: The thermoacidophilic and chemolithotrophic archaeon Acidianus ambivalens is routinely grown with sulfur and CO2-enriched air. We had described a membrane-bound, tetrathionate (TT) forming thiosulfate:quinone oxidoreductase. Here we describe the first TT hydrolase (TTH) from Archaea. Results: Ac. ambivalens cells grown aerobically with TT as sole sulfur source showed doubling times of 9 h and final cell densities of up to 8 x 108 ml-1. TTH activity (≈ 0.28 U/mg protein) was found in cell-free extracts of TT-grown but not of sulfur-grown cells. Differential fractionation of freshly harvested cells involving a pH shock showed that about 92 % of the TTH activity was located in the pseudo-periplasmic fraction associated with the surface layer, while 7.3 % and 0.3 % were present in the soluble and membrane fractions, respectively. The enzyme was enriched 54-fold from the cytoplasmic fraction and 2.1-fold from the pseudo-periplasmic fraction. The molecular mass of the single subunit was 54 kDa. The optimal activity was at or above 95 ˚C at pH 1. Neither PQQ nor divalent cations had a significant effect on activity. The gene (tth1) was identified following N-terminal sequencing of the protein. Northern hybridization showed that tth1 was transcribed in TT-grown cells in contrast to a second paralogous tth2 gene. The deduced amino acid sequences showed similarity to the TTH from Acidithiobacillus and other proteins from the PQQ dehydrogenase superfamily. It displayed a beta-propeller structure when being modeled, however, important residues from the PQQ binding site were absent. Conclusions: The soluble, extracellular and acidophilic TTH identified in TT-grown Ac. ambivalens cells is essential for TT metabolism during growth but not for the downstream processing of the TQO reaction products in S˚-grown cells. The liberation of TTH by pH shock from otherwise intact cells strongly supports the pseudo-periplasm hypothesis of the S-layer of Archaea.